2018
DOI: 10.1016/j.neuron.2018.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Reductions in Excitatory Input to the Nucleus Accumbens Underlie Food Consumption

Abstract: Reward-seeking behavior is regulated by a diverse collection of inputs to the nucleus accumbens (NAc). The information encoded in each excitatory afferent to the NAc is unknown, in part because it is unclear when these pathways are active in relation to behavior. Here we compare the activity profiles of amygdala, hippocampal, and thalamic inputs to the NAc shell in mice performing a cued reward-seeking task using GCaMP-based fiber photometry. We find that the rostral and caudal ends of the NAc shell are innerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 87 publications
(146 reference statements)
11
86
0
Order By: Relevance
“…These results suggest that the PVT BNST projection plays an opposing role in binge drinking behavior to the general PVT VGLUT2 glutamate neuron population ( Fig. 2g) and one that is not dependent on modulation of the general rewarding or aversive aspects of drug intake and consummatory behavior previously shown to be mediated by other major limbic outputs of the PVT such as the nucleus accumbens [18][19][20] .…”
Section: Figmentioning
confidence: 59%
“…These results suggest that the PVT BNST projection plays an opposing role in binge drinking behavior to the general PVT VGLUT2 glutamate neuron population ( Fig. 2g) and one that is not dependent on modulation of the general rewarding or aversive aspects of drug intake and consummatory behavior previously shown to be mediated by other major limbic outputs of the PVT such as the nucleus accumbens [18][19][20] .…”
Section: Figmentioning
confidence: 59%
“…These results suggest that the timing mechanism is optimized to detect reward delays for the temporal contiguity rather than the synchronicity of the onsets. The delayed peak may also account for the optimal duration of the tone at 0.5 s: the CS duration of 0.2 s was shorter than the optimal delay; and the longer CS duration was unable to effectively detect the strong activation of glutamatergic inputs that may have peaked soon after the CS onset and which may have waned thereafter (Reed et al, 2018). Along with this, the tuning curve for the tone duration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been therefore suggested that dopamine encodes a reward prediction error (RPE) signal (Schultz et al, 1997). The nucleus accumbens (NAc) is a major projection site of dopamine neurons (Menegas et al, 2017), and receives glutamatergic inputs from several brain regions including the amygdala and the hippocampus, showing transient activation to reward predictive cues (Reed et al, 2018). The convergent dopaminergic and glutamatergic signals regulate reward conditioning through N -methyl-D-aspartate type glutamate receptors (NMDARs) and dopamine D1 receptors (D1Rs) in the NAc (Kelley et al, 1997; Smith-Roe and Kelley, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the widespread availability of genetically-encoded calcium indicators and complementary in vivo imaging technologies has revolutionized the study of neural circuits and behavior. Among these technologies, fiber photometry has emerged as the least invasive, most accessible and affordable approach for recording neural activity in freely moving rodents 710 . Many intracellular signalling biosensors have been developed which utilize changes in Förster resonance energy transfer (FRET) between two fluorescent proteins 11 , in order to report levels or activity of second messengers, protein kinases, GTPases, post-translational modifications and protein-protein interactions 1215 .…”
Section: Introductionmentioning
confidence: 99%